G-quadruplex structures within the 3' UTR of LINE-1 elements stimulate retrotransposition. - Sahakyan, A; Murat, P; Mayer, C; Balasubramanian, S (Nature Publishing Group, 2017)
Long Interspersed Nuclear Elements (LINEs) are ubiquitous transposable elements in higher eukaryotes that play a significant role in shaping genomes due to their abundance. Here, we report that guanine-rich sequences in the 3’-UTR of hominoid-specific LINE-1 elements are coupled with retrotransposon speciation and contribute to retrotransposition through the formation of G-quadruplex (G4) structures. We demonstrate that stabilising the G4 motif of a human-specific LINE-1 element with small-molecule ligands stimulates retrotransposition.